Segmentation Using Wavelet And GVF Snake. - Foon, Dah Way; Rajeswari, Mandava; Ramachandram, Dhanesh (2005)
The Gradient Vector Flow (GVF) snake is a popular technique to segment object in image processing. Its advantages arc insensitivity to contour initialization and its ability to deform into highly concave part of the object compared to other deformable contour models.